ETIKA BISNIS AL-GHAZALI DAN ADAM SMITH DALAM PERSPEKTIF ILMU BISNIS DAN EKONOMI - AM. M. Hafidz MS.; H. Samíani Syaíroni; Marlina (JURNAL PENELITIAN, 2012)
This study was to explore: (1) the construction of business ethics that was formulated by al-Ghazali and Adam Smith, (2) the similarities and differences between the two menís business ethics, and (3) the relevance of their business ethics to the world modern business and economics. Business ethics constructed by al-Ghazali and Smith in the plains of praxis is not much different. Business ethics constructs built by al-Ghazali based on principles such as good faith orientation of the world and the hereafter, honesty, self-interest and social balance, and proper behavior / deeds. On another side, business ethics constructs built by Smith, based on fairness, altruism, justice and liberal (economic freedom). Good business ethics are introduced by both highly relevant to be used as a reference staple in modern business ethics.